Puma / Ahmad Idham Hakimi Mohd Zulkifli - Mohd Zukifli, Ahmad Idham Hakimi (2021)
Puma SE, dba Puma, is a German multinational corporation headquartered in Herzogenaurach, Bavaria, Germany, that designs and manufactures athletic and casual footwear, clothing, and accessories. Puma is the world's third-largest sporting goods company Rudolf Dassler founded the company in 1948. Rudolf Dassler and his brother Adolf Adi Dassler founded Gebrüder Dassler Schuhfabrik in 1924. (Dassler Brothers Shoe Factory). The two brothers' relationship weakened to the point that they decided to split in 1948, becoming two independent companies, Adidas and Puma. Today, both companies are headquartered in Herzogenaurach, Germany. Since 1986, Puma has become a publicly traded stock. Bjrn Gulden, a retired football player, has been the company's CEO since July 1, 2013. (chief executive officer). Following his separation from his brother, Rudolf registered his new business as Ruda (derived from Rudolf Dassler, as Adidas was based on Adi Dassler), but later renamed it to Puma.